Congestion management in deregulated power system using hybrid cat-firefly algorithm with TCSC and SVC FACTS devices. Issue 5 (5th September 2016) - Avudayappan, Naraina; Deepa, S.N.
Abstract : Purpose: The loading and power variations in the power system, especially for the peak hours have abundant concussion on the loading patterns of the open access transmission system. During such unconditional state of loading the transmission line parameters and the line voltages show a substandard profile, which depicts exaction of congestion management of the power line in such events. The purpose of this paper is to present an uncomplicated and economical model for congestion management using flexible AC transmission system (FACTS) devices. Design/methodology/approach: The approach desires a two-step procedure, first by optimal placement of thyristor controlled series capacitor (TCSC) and static VAR compensator (SVC) as FACTS devices in the network; second tuning the control parameters to their optimized values. The optimal location and tuning of TCSC and SVC represents a hectic optimization problem, due to its multi-objective and constrained nature. Hence, a reassuring heuristic optimization algorithm inspired by behavior of cat and firefly is employed to find the optimal placement and tuning of TCSC and SVC. Findings: The effectiveness of the proposed model is tested through simulation on standard IEEE 14-bus system. The proposed approach proves to be better than the earlier existing approaches in the literature. Research limitations/implications: With the completed simulation and results, it is proved that the proposed scheme has reduced the congestion in line, thereby increasing the voltage stability along with improved loading capability for the congested lines. Practical implications: The usefulness of the proposed scheme is justified with the computed results, giving convenience for implementation to any practical transmission network. Originality/value: This paper fulfills an identified need to study exaction of congestion management of the power line.